Independence day [videorecording (Blu-Ray)] - Devlin, Dean; Emmerich, Roland; Smith, Will, 1968-; Pullman, Bill; Goldblum, Jeff, 1952-; McDonnell, Mary; Hirsch, Judd; Colin, Margaret, 1958-; Quaid, Randy, 1950-; Loggia, Robert; Rebhorn, James, 1948-2014; Fierstein, Harvey, 1952-; et al. (20th Century Fox Home Entertainment, 2016)
On July 2nd, communications systems worldwide are sent into chaos by a strange atmospheric interference. At first thought to be meteors, the United States military suspect that a number of enormous alien spacecraft are on a collision course with Earth. After attempts to communicate with the aliens go nowhere, David Levinson, an ex-scientist turned cable technician, discovers that the aliens are going to attack major points around the globe in less than a day. On July 3rd, the aliens all but obliterate New York, Los Angeles, and Washington. Survivors set out towards Area 51, a strange government testing ground where it is rumored the military has a captured alien spacecraft of their own. The survivors devise a plan to fight back against the killing aliens, and July 4th becomes the day humanity will fight for its freedom.